Analyzing Use of the Graduate Record Examinations® General Test in Doctoral Nursing Education: Start, Stop, Continue, or Modify?. Issue 1 (January 2020) - Chicca, Jennifer
Abstract: AIM: The purpose of this study was to analyze uses of the Graduate Record Examinations® (GRE) General Test in doctoral nursing education. BACKGROUND: Doctoral study is a costly (time, money, resources, effort) investment for both students and institutions alike, and it is imperative students who are likely to succeed are admitted. Admission criteria such as the GRE General Test must be examined for appropriate use and necessity. METHOD: Literature regarding uses of the GRE General Test in doctoral nursing education was analyzed versus GRE General Test publisher evidence-based uses and guidelines while considering test psychometrics. RESULTS: Although the GRE General Test is widely used in doctoral nursing program admissions, it appears it is often not used according to evidence-based guidelines or uses. Notably, crucial self-validations are infrequent. CONCLUSION: Self-validations are essential when determining if doctoral nursing programs should start, stop, continue, or modify their use of the GRE General Test. Admission criteria analyses may help streamline admission processes and remove some unnecessary costs in doctoral education. Abstract : Supplemental digital content is available in the text.